The Interpretation of Bigger Thomas’ Dream and the Conflict in the “Native Son” by Richard Wright - Fradita Kasturi Rahayuningsih (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
Discrimination is often found in the society and many authors make discrimination as their main theme. One of the authors wrote their work with discrimination as their theme is Richard Wright in Native Son. This paper aims to discuss and analyze the conflict that appears due to discrimination which happens in the novel, also to interpret the dream that the main character had. The data was taken from the novel entitled Native Son by Richard Wright by using observation method and psychoanalysis approach. From the discussion and the analysis, it is found discrimination can cause several conflicts which lead to the psychological state of the main character. Keywords: discrimination, conflict, dream, interpretation